INFLUENCE OF OCCUPATIONAL HEALTH SAFETY (OHS) CULTURE, COMMITMENT MANAGEMENT, OHS TRAINING ON OHS PERFORMANCE IN OIL & GAS CONTRACTORS COMPANY IN BATAM ISLAND - Alden Nelson; Yedin Arianto Zega (Journal of Business Studies and Management Review, 2021)
Indonesia has very promising oil and gas potential to be exploited, including in Riau Islands province which has 15 oil and gas companies operating and 4 of them are already in production. Batam Island is part of the Kepulauan Riau province and there are oil and gas fabrications in it which are exported out from Batam Island. This fabrication is closely related with occupational safety and health. Respondents in this study were obtained from 261 employees work in the fabrication company or oil and gas contractor. Data processed using Statistical Package for Social Science (SPSS) version 24. The research of this method used non probability sampling where sampling techniques does not provide equal opportunities for each member of the population to be selected as a sample. The results of this study illustrated that OHS culture and management commitment have significant positive effect on occupational health safety performance but OHS training does not have significant effect.